Subspecies and Distribution. M.m.miurusOsgood,1901—KenaiPeninsula,Alaska,USA. M.m.anderson:Rand,1945—knownonlyfromthetypelocalityinWNorthwestTerritories,Canada. M.m.cantatorR.M.Anderson,1947—WrangellMtsofAlaska,USA,andSWYukon,Canada. M.m.murieiNelson,1931—NAlaska,USA,andmostofYukon,Canada. M. m. oreas Osgood, 1907 — S Alaska, USA. in Cricetidae - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
Subspecies and Distribution. M.m.miurusOsgood,1901—KenaiPeninsula,Alaska,USA. M.m.anderson:Rand,1945—knownonlyfromthetypelocalityinWNorthwestTerritories,Canada. M.m.cantatorR.M.Anderson,1947—WrangellMtsofAlaska,USA,andSWYukon,Canada. M.m.murieiNelson,1931—NAlaska,USA,andmostofYukon,Canada. M. m. oreas Osgood, 1907 — S Alaska, USA. Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 334, DOI: 10.5281/zenodo.6707142